Au fond de l’eau : histoires sociales et représentations environnementales d’un bassin versant agricole - Sandrine Petit (Territoire en Mouvement, 2017)
The Sorme lake was created in 1970 by damming the so-called river. Afterwards, it becomes a drinking water resource for the towns of Le Creusot and Montceau-les-Mines. In the 1980’s, water eutrophication appeared. Then, in 1990’s, an action programme was jointly elaborated between managers of the lake and farmers. Despite the fact that farms were brought into compliance with environmental standards, the water quality is still to be improved regarding organic matter and phosphorus, consequently a new action programme is being prepared. I analyse the historical transformation of the problem of water management addressed and the sphere of actors involved for solving it. The local actors hardly refer to a common story and share solutions as their representations of the lake differ. Water managers “naturalize” the lake territory when farmers refer to its man-made origin and “domesticate” water. An alternative water management is based on a common good approach sharing representations, knowledge and responsibilities.